Phenotypic drift in metastatic progression of breast cancer: A case report with histologically heterogeneous lesions that are clonally related. Issue 12 (27th August 2020) - Kutasovic, Jamie R.; McCart Reed, Amy E.; Sokolova, Anna; Jayanthan, Janani; Da Silva, Leonard; Simpson, Peter T.; Lakhani, Sunil R.
Abstract: Breast cancer metastasis to the stomach is rare; invasive lobular carcinoma has a predilection to spread to the gastrointestinal system and is morphologically similar to primary diffuse gastric carcinoma. This case highlights heterogeneous metastatic progression and that documentation of heterogeneity is important for informing future treatment strategies and prognostication. Abstract : Breast cancer metastasis to the stomach is rare; invasive lobular carcinoma has a predilection to spread to the gastrointestinal system and is morphologically similar to primary diffuse gastric carcinoma. This case highlights heterogeneous metastatic progression and that documentation of heterogeneity is important for informing future treatment strategies and prognostication.